2009
DOI: 10.1007/s10936-009-9129-z
|View full text |Cite
|
Sign up to set email alerts
|

Gender Bender: Gender Errors in L2 Pronoun Production

Abstract: To address questions about information processing at the message level, pronoun errors of second language (L2) speakers of English were studied. Some L2 pronoun errors-he/she confusions by Spanish speakers of L2 English-could be due to differences in the informational requirements of the speakers' two languages, providing a window into the composition of the preverbal message that guides grammatical encoding during language production. To study this, Spanish and French speakers of L2 English were made to answe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 39 publications
(39 reference statements)
0
17
0
Order By: Relevance
“…However, gender errors ceased to occur as learners' language proficiency increased, which is not true with Chinese-English bilinguals. Besides, the error rates found in Dong and Jia (2011) are much higher than those reported in Antón-Méndez (2010a, 2010b with Dutch-English, Spanish-English and Italian-English bilinguals. Using data in the LINDSEI corpus (Louvain International Database of Spoken English Interlanguage corpus), Chen (2004) found that Chinese EFL learners' gender error rate was 17.65 %, much higher than that of Japanese and French EFL learners whose native language distinguishes thirdpersonal pronouns for male and female antecedents (error rate: 4.2 %, 0.92 %, respectively).…”
Section: Introductionmentioning
confidence: 57%
“…However, gender errors ceased to occur as learners' language proficiency increased, which is not true with Chinese-English bilinguals. Besides, the error rates found in Dong and Jia (2011) are much higher than those reported in Antón-Méndez (2010a, 2010b with Dutch-English, Spanish-English and Italian-English bilinguals. Using data in the LINDSEI corpus (Louvain International Database of Spoken English Interlanguage corpus), Chen (2004) found that Chinese EFL learners' gender error rate was 17.65 %, much higher than that of Japanese and French EFL learners whose native language distinguishes thirdpersonal pronouns for male and female antecedents (error rate: 4.2 %, 0.92 %, respectively).…”
Section: Introductionmentioning
confidence: 57%
“…In view of this, one would have expected to find these speakers making gender errors also in the inanimate conditions when mistakenly forgetting to implement semantic agreement and encode the possessor's gender on the possessive pronoun. Such errors, due to insufficient automatization of L2 procedures, should have surfaced in the absence of any further influence from syntactic agreement as more or less random gender errors, as was observed for nominative pronouns in Spanish–English L2 speakers (Antón-Méndez, 2010). One possible way to interpret this lack of errors with inanimate possessums is to assume that the L2 process of semantic gender agreement with the anaphoric antecedent has been fully automatized.…”
Section: Discussionmentioning
confidence: 97%
“…Being again a matter of automatization ("excess" automatization in this case), here too the resulting errors are more likely to surface during spoken language production than in samples of edited written production. These errors, being the result of an automatic process inappropriately applied, can inform and constrain models of bilingual production, and can also be a useful source of data to investigate more general processes of language production (Antón-Méndez, 2010). This article reports an exploration of one particular L2 error which may result from a mix of insufficient automatization and excess automatization at different processing levels: 3rd person singular possessive pronoun gender errors of Italian and Spanish native speakers in L2 English.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Occasional performance breakdowns in mature, proficient language users have traditionally been used in psycholinguistics to provide insights onto the mechanisms of “normal” language processing, its preferences, and limitations (Fromkin, 1984; Garrett, 1988; Pritchet, 1988). Learners’ errors can be just as useful in that they may offer insights onto how learners’ grammatical representations and processing develop across time (e.g., children's overgeneralization errors; Marcus et al, 1992) and how they are affected by factors such as age of acquisition, cognitive maturation, and cross-linguistic influences (e.g., Antón-Méndez, 2010).…”
mentioning
confidence: 99%